Rasio Profitabilitas dalam Mengukur Kinerja Keuangan pada Apotek Syakir Farma - Susantika, Melani; Tijjang, Bakhtiar; Hasan, Hamida; Rifani, Riza Amalia (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This research aims to determine and analyze financial performance using profitability ratios at the Syakir Farma Pharmacy Palanro Village in accordance with industry standards. The analytical method used in this research is a quantitative descriptive approach. Quantitative data in the form of a sample of the financial report of the Syakir Farma Pharmacy Palanro Village in the form of a balance sheet and profit and loss for the 2020-2022 period. The data analysis method in this research uses profitability ratios. The results of this research show that the financial reports at the Syakir Farma Pharmacy, which were assessed through Gross Profit Margin (GPM) analysis, are in very good condition and comply with industry standards. In 2020 the value achieved by GPM was 36.44%, in 2021 it was 34.12% and in 2022 it was 34.17%. The financial performance measured through Net Profit Margin (NPM) analysis is in fairly good condition according to industry standards. The value achieved by NPM in 2020 was 17.82%, in 2021 it was 20.09% and in 2022 it was 19.99%. Then the financial performance measured through Return On Asset (ROA) analysis is in very good condition according to industry standards, the value achieved by ROA in 2020 was 27.64%, in 2021 it was 37.54% and in 2022 it was 41.05%. And financial performance as measured through Return On Equity (ROE) analysis is in very good condition according to industry standards with the value achieved in 2020 amounting to 45.04%, in 2021 amounting to 56.04% and in 2022 amounting to 60.11%. It can be seen that the financial performance of Syakir Farma Pharmacy Kel. Palanro uses the profitability ratio method in accordance with industry standards.